Assessment of Energy Efficiency in Beverage Industry - Mtebwa, Mahamudu H.; Ichwekeleza, Wiston Y. (Tanzania Journal of Engineering and Technology, 2022)
The brewery industry has a significant contribution to the national income. However, it is also associated with energy-intensive processes and pollution. In this work, the energy efficiency assessment of the largest brewery in Tanzania i.e., Tanzania Breweries Limited has been conducted. Energy consumption analysis was conducted according to IEEE SA 739-1995. Important parameters used to assess brewery energy efficiency were boiler efficiency and losses, equipment energy productivity as well as load factor. It was found that the main energy consumers are packaging (54.63%), brewing (29.30%) and utilities (15.17%). More importantly, it was found that about 68% of the brewery energy demand is thermal energy which is supplied by the boiler whose efficiency (62%) is significantly lower than the expected value of 94-95%. Load factor analysis showed that the equipment of both brewing and packaging line 4 are significantly oversized. Furthermore, energy productivity of 45.5 kWh/L of beer is significantly higher than the industry minimum of 23.6 kWh/L. Keywords: Brewery, Energy efficiency, Energy productivity The brewery industry has a significant contribution to the national income. However, it is also associated with energy-intensive processes and pollution. In this work, the energy efficiency assessment of the largest brewery in Tanzania i.e., Tanzania Breweries Limited has been conducted. Energy consumption analysis was conducted according to IEEE SA 739-1995. Important parameters used to assess brewery energy efficiency were boiler efficiency and losses, equipment energy productivity as well as load factor. It was found that the main energy consumers are packaging (54.63%), brewing (29.30%) and utilities (15.17%). More importantly, it was found that about 68% of the brewery energy demand is thermal energy which is supplied by the boiler whose efficiency (62%) is significantly lower than the expected value of 94-95%. Load factor analysis showed that the equipment of both brewing and packaging line 4 are significantly oversized. Furthermore, energy productivity of 45.5 kWh/L of beer is significantly higher than the industry minimum of 23.6 kWh/L.